TINGKAT INSIDENSI PEMOTONGAN SAPI BETINA BUNTING DI RUMAH POTONG HEWAN KOTA AMBON - Demianus F. Souhoka; Astri D. Tagueha; Rajab Rajab (Jurusan Peternakan Fakultas Pertanian Universitas Pattimura, 2020)
The objectives of this research was to investigate the incidence of pregnant cows slaughtered and to explore incidence level of foetal wastage at the abattoirs in Ambon town. Data collection were held at the abattoirs from 6 to 27 october 2018. The notion of the research was a case study investigation. The variables were number of cattle slaughtered, characteristics of cows slaughtered [number, body weight an origin], and characteristics of foetal wastage [number, sex, body weight and body length]. Data were descriptively analyzed and the graphically presented. T test was also used to compare body measures of fetuses based on its sex. The results showed that incidence of pregnant cows slaughtered was 34% which is higher than the tolerance limit 12%. There were 53 fetuses found consisted of 30 females and 23 males. Average fetuses weight was 2160.17 grams and 32.68 cm body length.